Experiences of Accidental Project Managers - An Australian Survey - Baccarini, David; Darrell, V. (Project Management Global, 2006)
The accidental project manager is part of project management folklore. Many project managers enter into project management by accident, with little preparation for this challenging role. This paper presents the results of research into the experiences of accidental project managers in Perth, Western Australia, based on questionnaires from 46 individuals principally from the government sector. The key conclusions are: project managers are principally selected due to their technical knowledge or expertise; there is a gap between the skills the project manager possesses and the skills requiredof the role; organisations make personal development opportunities available to accidental project managers principally through training and experience; there is a lack of project management methodologies, tools and techniques to support accidental project managers